The most commonly used scales for assessing patients with chronic venous disease and ulcers - Mościcka, Paulina (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2025)
According to epidemiological data, venous disorders, at various stages of severity, affect 3% of adult Poles. In the most advanced form, they cause the development of venous ulcers. For over 20 years, scales have been recommended for classifying and assessing the severity of chronic venous disorder (CVD) and chronic venous insufficiency (CVI). These classifications have been improved over the years and are valuable instruments used in the care of patients with venous disorders and ulcers. The scales most commonly used by clinicians appear to be: the Clinical-Etiology-Anatomic-Pathophysiologic (CEAP) clinical classification system, the Venous Clinical Severity Score (VCSS) and the Villalta scale. The aim of our study was to describe the recommended tools for classifying, diagnosing and assessing the severity of venous disease and venous ulcers.